Upcycling of Agro-Food Chain By-Products to Obtain High-Value-Added Foods - Graziana Difonzo; Silvia Grassi; Maria Paciulli (Foods, 2022)
Rising challenges for food innovation and environmental issues have led to an increased interest in bio-economy and more sustainable food production [...]